Kesepaduan falsafah sains AL-Qur’an dalam kurikulum sekolah rendah sebagai asas pembentukan masyarakat hadhari di Malaysia - Yahaya Bin Jusoh; Azhar Bin Muhammad (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2010)
The civilizational (hadhari) community could be shaped in the Malaysian community through a formal education system. The approach which uses Qur’anic science philosophy combines social science and natural science with theological knowledge in the primary school curriculum could also realize and establish this community. It is undeniable with the emergence of modern science in the era of globalization causes the principle thinking of Qur’anic science philosophy to be isolated. The teachings of social science and natural science started to be separated from theological knowledge of which is more to the direction of materialistic elements compared to spiritual elements. Through reforming the national curriculum, primary school students, as the new generation, will form the foundation of thought in Qur’anic science philosophy which focuses on the existence of a civilizational community. This paper work will present the importance of this philosophy in the national education system exclusively in the Integrated Curriculum for Primary Schools (KBSR) which is the foundation to create the civilizational community.